(untitled) (Proceedings of the International Conference on Education, 2020)
The purpose of this research is to study the implementation, and strategy, moreover, to evaluate strategy for the best practice in information and communication technology (ICT) from the schools with the best practice. The research area is the case study of primary school in Chaiyaphum province with excellent ICT implementation. A group of informants includes personnel and people involved in ICT. The method of conducting research is qualitative research processes such as interviews, group discussions, and observation. Tools used include interview record form, group discussion record form, and observation record form by using content analysis with the Application Program to organize data for summarizing research results. The research found that the implementation of ICT consists of 6 components as follows: management in educational institutions, infrastructure, instruction, learning process, learning resources, and cooperation of the public, private and community sectors. For the strategy of being excellent, the executive must study ICT policies to implement the policy into practice and apply in the planning of administration. Furthermore, developing the technology skill of personnel by using participatory processes both inside and outside educational institutions. The strategy was evaluated and found that the standards, appropriateness, and feasibility are at a high level that can be a guideline for the development of ICT.